2023
DOI: 10.3390/diagnostics13071336
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Effects on Muscle Fatigue in Sport in Active Adults with Long COVID-19: An Observational Study

Abstract: Long COVID-19-related changes in physiology includes alterations in performing muscle work as fatigue. Data available do not allow us to define the usefulness of physical activity to attenuate long COVID-19 functional modifications. The present observational study investigates the effects of physical activity on the perception of fatigue, maximum power output, sleep, and cognitive modifications in subjects affected by long COVID-19, distinguishing between active and sedentary subjects. The data demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This prescription should be preceded by an initial consultation to detect "red flags", e.g., comorbidities and risk of PESE, an autonomic dysfunction which may contraindicate the practice of physical activity, sometimes described as "harmful" [7,20]. In long COVID, PESE was found in 8-75% of patients according to the literature [98][99][100], which explains why some authors preferred to proscribe physical activity in long COVID [7,101], supported by the results of a recent cross-sectional study in which 75% of participants declared worsening symptoms with physical activity [102]. However, our results showed that an adapted physical activity performed in a safe, appropriate and individualized manner seems to be relevant for a subgroup of patients without PESE at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prescription should be preceded by an initial consultation to detect "red flags", e.g., comorbidities and risk of PESE, an autonomic dysfunction which may contraindicate the practice of physical activity, sometimes described as "harmful" [7,20]. In long COVID, PESE was found in 8-75% of patients according to the literature [98][99][100], which explains why some authors preferred to proscribe physical activity in long COVID [7,101], supported by the results of a recent cross-sectional study in which 75% of participants declared worsening symptoms with physical activity [102]. However, our results showed that an adapted physical activity performed in a safe, appropriate and individualized manner seems to be relevant for a subgroup of patients without PESE at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…For those who suffered from it, a structured pacing protocol was efficient to reduce PESE episodes and improved overall health [103]. Thus, the exercise rehabilitation program must be progressive and adapted to each patient, respecting their difficulties and limitations in order to avoid any risk of PESE [1,99,104]; this state of PESE was described as "transient" by Coscia et al (2023) and the exploration of the signs of PESE by clinical assessment, questionnaire or CPET should be regularly performed in order to offer a suitable care [100]. To this end, the most recommended questionnaire is the DePaul Symptom Questionnaire-Post-Exertional Malaise (DSQ-PEM) [105].…”
Section: Discussionmentioning
confidence: 99%
“…The study of this homogeneous population, which was very effectively and continuously followed up by the Sports Medicine Service of two Italian hospitals (Inniken and Brunek, Bolzano), has shown that good fitness, both before and during the illness, combined with strong motivation, can restore the pre-COVID state in about 92% of the subjects within one year, with very little statistical variation within the various groups. 34 In the UK, approximately 10% of elite athletes experienced symptoms of Long-COVID, similar to the general population for more than one month. 35 However, some data from US college athletes showed a much lower prevalence of Long-COVID than in the general population (0.8% at one month).…”
Section: Difficulties Limitations and Bias Of Long-covid Studiesmentioning
confidence: 99%
“… 33 In support of that, there is also a paper. 34 This observational study by our research group was carried out on athletes and/or ski instructors (n=506, including 138 women) from a population (n=6000) who were first infected with SARS-2-CoV-2 and subsequently manifested typical symptoms of Long-COVID and were followed up for one year. The study of this homogeneous population, which was very effectively and continuously followed up by the Sports Medicine Service of two Italian hospitals (Inniken and Brunek, Bolzano), has shown that good fitness, both before and during the illness, combined with strong motivation, can restore the pre-COVID state in about 92% of the subjects within one year, with very little statistical variation within the various groups.…”
Section: Difficulties Limitations and Bias Of Long-covid Studiesmentioning
confidence: 99%
“…Several dimensions of long COVID fatigue have been distinguished in the literature, which has led to it being inconsistently defined. 11 For example, several studies investigating long COVID fatigue lack a precise definition, 12 and others display variability in how fatigue is defined, encompassing dimensions of physical fatigue, 13,14 cognitive fatigue, 5,15 post-exertional malaise, 7,16 sleep-related fatigue, 17 or general fatigue. 18 As well as the different dimensions of fatigue, further distinction can be made between fatigue that occurs in the context of a specific activity or task and fatigue that is experienced over weeks or months.…”
Section: Introductionmentioning
confidence: 99%